Gaming Instead of Training? Exergaming Induces High-Intensity Exercise Stimulus and Reduces Cardiovascular Reactivity to Cold Pressor Test - Ketelhut, Sascha; Ketelhut, Reinhard G.; Kircher, Eva; Röglin, Lisa; Hottenrott, Kuno; Martin-Niedecken, Anna Lisa; Ketelhut, Kerstin (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The present study compares an acute heart rate controlled exergame training with a moderate endurance training (ET). In addition to physiological responses, the cardiovascular reactivity to the cold pressor test (CPT) is assessed. Methods: Twenty-seven healthy participants aged 25 ± 4 years (48% female; BMI 23.0 ± 2.1 kg/m2) completed both an ET on a treadmill and training in the ExerCube (ECT). Heart rate (HR) and oxygen consumption were recorded during both training sessions. Before and after both exercise sessions, the hemodynamic reactivity to a CPT was determined. Results: During ECT, HR, oxygen consumption, energy expenditure, and the metabolic equivalent of the task were significantly higher than those obtained during ET (p<0.001). With regard to the CPT, the participants showed significantly lower responses in peripheral systolic (p=0.004) and diastolic blood pressure (p=0.009) as well as central systolic (p=0.002) and diastolic BP (P=0.01) after ECT compared to ET. The same was true for pulse wave velocity (p=0.039). Conclusion: The ECT induces a significantly higher exercise stimulus compared to the ET. At the same time, it attenuates hemodynamic stress reactivity. The ECT present a relevant training stimulus that modulates cardiovascular reactivity to stress, which has been proven as a predictor for the development of hypertension.